Formation of radial optical structures on a circular laser recording system - Косяк, І. В.; Цубін , О. А. (Інститут проблем реєстрації інформації НАН України, 2024)
An analysis and research of the systems for the formation of planar optical elements has been carried out. Features of development and construction of circular laser recording systems are considered. The imp-lementation of the formation of radial optical structures by a laser optical disk recording system is proposed. To obtain a certain pattern on the surface of a glass substrate, the photolithography method is used, which is widely used in microelectronics and other types of micro-technologies, as well as in the production of optical encoders and coding discs. There are three types of photolithography: contact; with a gap; projection Recently, the technology of laser lithography, the so-called method of direct laser recording in photoresist, has been developing more and more actively. This technology makes it possible to manufacture and replicate a wide range of different optical structures and micro-optical elements. The analysis of research and publications shows that a great deal of attention is paid to the problem of developing laser lithography tools and technologies. From this follows the task of research — conducting an experimental study of recording radial optical structures on photoresist on a circular laser recording system. The formation of radial optical structures by the method of direct laser recording was carried out on the basis of an active laser recording station, which was created at the Institute of Information Registration Problems of the National Academy of Sciences of Ukraine. With the technology of direct laser recording on a circular laser recording system, in contrast to the technology of laser recording of photo templates in Cartesian coordinates, exposure is carried out with a focused beam at very high scanning speeds of 0,3–0,6 m/s. In manufacturing the optical structure element, the substrate with the light-sensitive material rotates continuously, while the recording beam slowly moves in the radial direction from the center to the edge according to a given pattern. An experimental study of the recording of radial optical structures by photoresist on a circular laser recording system was performed. It is shown that the developed data preparation system allows recording radial optical structures of arbitrary shape. Increasing the resolution of recording elements of optical structures and improving optical, mechanical, and electronic assemblies remain urgent tasks. Fig.: 2. Refs: 12 titles.